Liquidity Provision and the Organizational Form of NYSE Specialist Firms - Coughenour, Jay F.; Deli, Daniel N. (Journal of Finance, 2002)
ABSTRACT We examine the influence of NYSE specialist firm organizational form on the nature of liquidity provision. We compare closely held firms whose specialists provide liquidity with their own capital to widely held firms whose specialists provide liquidity with diffusely owned capital. We argue that specialists using their own capital have a greater incentive and ability to reduce adverse selection costs, but face a greater cost of capital. Differences in the proportion of spreads due to adverse selection costs, large trade frequency, the sensitivity between depth and spreads, and price stabilization support this argument.